The diet of woodland caribou populations in west-central Alberta - Thomas, Donald C.; Edmonds, E. Janet; Brown, W. Kent (Rangifer, 1996)
The diet of woodland caribou (Rangifer tarandus caribou) populations in the foothills and Rocky Mountains of west-central Alberta was estimated by microhistological analyses of feces collected in winter and summer. In winter, terrestrial lichens averaged 60-83% of fecal fragment densities in both areas. In the mountains, decreasing proportions of terrestrial lichens and increasing proportions of conifer needles and moss indicated decreasing accessibility of forage because of deeper/harder snow. Apparent diets in summer were dominated by Salix spp., sedges, and lichens. However, forb inflorescences and stems were largely undetected by the microhistological technique and results for summer samples must be interpreted accordingly. We conclude that the conservation and management of forest ecotypes of caribou must include options of lichen-rich habitats as a major component of management plans.